The identification and characterisation of a novel Apoptotic Gene,Snama, in drosophila melanogaster - Mather, Arshad Saleh (My University, 2006)
SNAMA is the Drosophila melanogaster homologue of a group of proteins that are known to bind p53 and the retinoblastoma protein (Rb). This multi domain protein consists of a conserved N-terminal domain called Domain With No Name (DWNN), a zinc finger, a cysteine rich RING finger-like domain, a probable p53 binding region, and a glutamic acid-rich and lysine-rich region. These associated domains indicate that SNAMA plays an important regulatory role in the cell and may function in RNA processing and in apoptosis. The DWNN domain was first identified in Cytotoxic T-cell resistant Chinese hamster ovary (CHO) cells using promoter trap mutagenesis to screen for genes involved in apoptosis. Subsequently, this domain was identified in other eukaryotic organisms including animals and plants. The SNAMA transcriptional unit consists of 9 exons and 8 introns that code for a 1231 amino acid protein with the 76 residue N-terminal DWNN domain. The DWNN domain has a 23.5% sequence identity to the ubiquitin protein and a predicted folded structure similar to ubiquitin. Western blots identified multiple bands indicative of ubiquitin tagged proteins. Taken together this suggests a role in the ubiquitin pathway either as an ubiquitin domain protein or the DWNN domain of SNAMA tagging other proteins. The cysteine rich RING finger-like domain has a histidine to serine substitution at the fourth position of the putative RING finger and represents a distinct class of RING finger-like proteins that could have ubiquitin ligase activity. Northern blot analysis identified a single 4.6 kbp transcript expressed abundantly throughout development early in embryogenesis but reduced in older embryos and in adult male and females. SNAMA probably interacts with Dmp53 as a suppressor of apoptosis or a negative regulator of an activator of apoptosis. It is a vital gene required for development, as the mutant P-element insertion line in which the Pelement is inserted in the first intron of SNAMA is lethal when homozygous. Acridine orange staining of these mutant flies showed a direct correlation between the presence of SNAMA and apoptosis. An increase in the levels of apoptosis occurred in embryos with relatively low levels of SNAMA expression. The mode of this action is either direct, or via other proteins that are involved in the apoptotic pathway.
Student Number : 9105022E - PhD thesis - School of Molecular and Cell Biology - Faculty of Science
Keywords: cell cycle; RNA processing; p53; retinoblastoma protein (Rb); DWNN